A versatile ferrocene-containing material as a p-type charge generation layer for high-performance full color tandem OLEDs. Issue 99 (24th November 2016) - Chang, Yu-Wei; Huang, Min-Jie; Lai, Cheng-Chang; Chang, Ching-Chih; Huang, Man-Ping; Liao, Chuang-Yi; Cheng, Chien-Hong
Abstract : A ferrocene derivative, DPAF, is developed as a p-type charge generation layer and gives excellent device performance for RGB tandem OLEDs. Abstract : A novel p-type charge generation material, DPAF, composed of a ferrocene core and a bis(biphenyl)amino group is designed and synthesized for application to tandem OLED devices. This molecular design not only enhances the thermal properties of ferrocene and the hole mobility, but also maintains its electrochemical stability. The red, green, and blue tandem OLEDs all give excellent device performance with low efficiency roll-off by using n-type C60 and p-type DPAFs as charge generation layers.